2021
DOI: 10.1007/s12369-021-00817-2
|View full text |Cite
|
Sign up to set email alerts
|

Robocalypse? Yes, Please! The Role of Robot Autonomy in the Development of Ambivalent Attitudes Towards Robots

Abstract: Attitudes towards robots are not always unequivocally positive or negative: when attitudes encompass both strong positive and strong negative evaluations about an attitude object, people experience an unpleasant state of evaluative conflict, called ambivalence. To shed light on ambivalence towards robots, we conducted a mixed-methods experiment with N = 163 German university students that investigated the influence of robot autonomy on robot-related attitudes. With technological progress, robots become increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…A small positive correlation between positive and negative views on humanoid robots has also been reported previously [11]. Similar attitude ambivalence has been reported in a mixed-methods study investigating participants' views about a specific robot [7]. It appears, therefore, that individuals can hold both positive as well as negative attitudes towards humanoid robots and that these are not necessarily mutually exclusive.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…A small positive correlation between positive and negative views on humanoid robots has also been reported previously [11]. Similar attitude ambivalence has been reported in a mixed-methods study investigating participants' views about a specific robot [7]. It appears, therefore, that individuals can hold both positive as well as negative attitudes towards humanoid robots and that these are not necessarily mutually exclusive.…”
Section: Discussionsupporting
confidence: 80%
“…Although many people make contact with increasingly common surgical robots [2], more interactive general attitude that individuals hold irrespective of whether they had been exposed to a robot. Such attitudes could be developed through information obtained from media such as films [7]. While acceptance is useful to explore or finetune functionality, morphology, and presentation of the robot, acceptability is more relevant to assess when investigating the use of robots in principle -thus more commonly at the very early stages of robot development.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, perceptions of personalized robots would not be univalent, but torn between two conflicting evaluations at once. This phenomenon is referred to as attitudinal ambivalence and may also affect perceptions of robots [71,72], especially when deemed autonomous [72]. Future research should take ambivalent attitudes towards robots into account when investigating the effects of personalization on HRI.…”
Section: Personalization Of Robots and Anthropomorphismmentioning
confidence: 99%
“…In fact, recent studies have demonstrated that people's attitudes toward the targeted object may be ambivalent and cannot be simply described as just negative or positive [21], which have been studied in various domains, such as artificial intelligence (AI) [22] and online private-information sharing [23]. In the healthcare context, a qualitative metasynthesis revealed the ambivalent nature of end users' attitudes toward robotics in motor rehabilitation, namely the dilemma between benefits (e.g., improvement in activities of daily life) and challenges (e.g., the fear of being controlled by robots) during the interaction with robotic devices [24].…”
Section: Introductionmentioning
confidence: 99%
“…In the healthcare context, a qualitative metasynthesis revealed the ambivalent nature of end users' attitudes toward robotics in motor rehabilitation, namely the dilemma between benefits (e.g., improvement in activities of daily life) and challenges (e.g., the fear of being controlled by robots) during the interaction with robotic devices [24]. In addition, several quantitative studies explored the relationship between ambivalent attitudes toward robots and other key variables through experiments, such as their mental abilities [13] and autonomy [21]. Therefore, it seems crucial to identify distinct clusters of attitudes toward robots in healthcare within a homogeneous population of interest, which will provide empirical insights into the development and potential future uses of healthcare robots in HRI research.…”
Section: Introductionmentioning
confidence: 99%